Research on few-shot handwriting identification based on Siamese networks - Wang, Xuyang; Xu, Chengzhi; Dong, Liuyuan; Xie, Ruizhen; Yang, Wanli (Zielona Góra: Uniwersytet Zielonogórski)
With the rise of the digital era, handwriting examination has become crucial for identity verification and document provenance. However, determining whether samples from different texts are written by the same person remains challenging. The challenge is greater in few-shot settings, where data are scarce and writing styles vary widely. Traditional methods often lack sufficient accuracy and robustness.
Keywords: handwriting identification; attention mechanism; Siamese network; feature library; few-shot learning